Gender Differences in Predictors of Self-Medication with Tranquillizers and Sleeping Pills: Results of the Population-Based Study in Serbia - Tripković Katica; Šantrić Milićević Milena; Odalović Marina (Sciendo, 2019)
Previous studies among the Serbian population concluded that the trend of self-medication with tranquillizers and sleeping pills requires deeper study. The objective is to identify gender differences in socio-demographic, health, and health service predictors of self-medication with tranquillizers and sleeping pills in a Serbian population of 15 years old and above.